2015
DOI: 10.1007/s10995-015-1851-6
|View full text |Cite
|
Sign up to set email alerts
|

The Association Between Health Insurance Coverage and Skilled Birth Attendance in Ghana: A National Study

Abstract: Skilled birth attendance (SBA) is a key health intervention used by roughly two-thirds of women in Ghana. The National Health Insurance Scheme (NHIS) provided by the Government of Ghana is widely expected to improve maternal health outcomes by removing financial barriers to health services. Using data from the 2011 national Ghana Multiple Indicator Cluster Survey implemented by the Ghana Statistical Services and UNICEF, we examine the effect of insurance on SBA using a multivariate logistic model, controlling … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
16
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 36 publications
3
16
1
Order By: Relevance
“…This finding is consistent with observations made in Ghana, a neighboring West African country that is undergoing similar transformative changes to expand health insurance coverage for its population. Using a nationally representative sample, Khan and Singh found that insurance coverage in Ghana increased the odds of SBA use by 47%. Several other studies conducted in Sub‐Saharan Africa have also found a positive relationship between insurance and access to maternal health services including SBA.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This finding is consistent with observations made in Ghana, a neighboring West African country that is undergoing similar transformative changes to expand health insurance coverage for its population. Using a nationally representative sample, Khan and Singh found that insurance coverage in Ghana increased the odds of SBA use by 47%. Several other studies conducted in Sub‐Saharan Africa have also found a positive relationship between insurance and access to maternal health services including SBA.…”
Section: Discussionmentioning
confidence: 99%
“…The dominant paradigm that prevails today in Sub-Saharan Africa in terms of accessing healthcare services is the user fee system (out-ofpocket payment), which is also one of the most widely used strategies to finance health delivery systems. [1][2][3] This approach has an enormous negative impact both financially and in terms of access to quality health care, 3 including maternal health services such as prenatal care, skilled birth attendance (SBA), and postnatal care. 4 The more a country relies on this kind of strategy, the more its citizens face scarcity 5 and financial hardship.…”
Section: Introductionmentioning
confidence: 99%
“…More than half of the pregnant women with malaria (14/21) had not taken any anti-malarials in the last 6 months. This could be due to low or late attendance of antenatal clinics in rural areas [ 41 , 42 ], regardless of provision of free medical care for pregnant women under the National Health Insurance Scheme [ 41 ]. Another possible reason is the availability of poor quality sulfadoxine–pyrimethamine; some SP drugs on the Ghanaian market have been found to be of low quality.…”
Section: Discussionmentioning
confidence: 99%
“…Another major limitation frequently discussed by authors (n = 13 studies) concerned recall bias [13,21,25,26,30,31,33,35,38,39,48,73,76], as information on insurance membership (exposure) and health status and/or health-service use (outcomes of interest) was often collected at different time points, not always allowing a perfect match between the two. Authors of studies relying on secondary data often discussed limitations due to the nature of the secondary data [15,19,21,27,32,33,36,37,39,49,55,56,58,64,67,77], including lack of information on specific covariates to refine model estimation; impossibility of checking the quality and/or accuracy of the data; and for one study relying on medical charts, with large amounts of missing data [65]. Finally, only eight authors (four from quasi-experimental studies [22,61,62,73] and four from observational studies [37,38,59,76]), acknowledged the impossibility of establishing a causal link between insurance and outcomes of interest due to the crosssectional nature of the data being used.…”
Section: Methodological Limitations Reported In the Included Studiesmentioning
confidence: 99%